1999
DOI: 10.1542/peds.103.2.e15
|View full text |Cite
|
Sign up to set email alerts
|

Chest Roentgenogram in the Evaluation of Heart Defects in Asymptomatic Infants and Children With a Cardiac Murmur: Reproducibility and Accuracy

Abstract: ABSTRACT. Objectives. To evaluate the reproducibility and the accuracy of pediatric radiologists' assessments of chest radiographs with respect to the presence or absence of heart defects in children with an asymptomatic heart murmur.Design. Ninety-eight children, ages 1 month to 15 years (median, 30.1 months), referred for evaluation of a heart murmur were consecutively included. They all had a standard chest radiograph and a color Doppler echocardiograph (CDE) performed. Six specialists in pediatric radiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 16 publications
1
8
0
4
Order By: Relevance
“…than for the group as a whole. We found the chest film to have similar sensitivity and specificity for CHD as those found in previous studies in older children [1,11], despite the concern that chest films performed during the first 24-48 hours following delivery may be particularly hmited in their ability to assess for CHD. In fact, wiien patients whose chest films were obtained during this time period were analyzed separately, the results did not differ significantly from those of the entire group.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…than for the group as a whole. We found the chest film to have similar sensitivity and specificity for CHD as those found in previous studies in older children [1,11], despite the concern that chest films performed during the first 24-48 hours following delivery may be particularly hmited in their ability to assess for CHD. In fact, wiien patients whose chest films were obtained during this time period were analyzed separately, the results did not differ significantly from those of the entire group.…”
Section: Discussionsupporting
confidence: 78%
“…Several studies have addressed the utility of the chest film as a screening tool for CHD in older infants and children presenting to pediatric cardiology outpatient clinics [1,9,[11][12][13]. These studies have demonstrated that the chest film does not appear to function as an adequate screening tool, and it does not appear to add significantly to a thorough history and physical examination in determining the hkelihood of CHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Semptomu olmaksızın kardiyak üfürümü olan infantlarda yapı-lan bir çalışmada telekardiyografinin kalp hastalığı varlığı veya yokluğunu ortaya koymada düşük doğruluk değeri olduğu gösterilmiştir (14). Yine benzer şekilde 120 infant kalp üfürümü yönünden değerlendirilmiş ve elektrokardiyografinin bu yaş grubunda kalp hastalığını ayırmada yetersiz olduğu vurgulanmıştır (15).…”
Section: -Cevabınız Evet Ise Hangi Yolla Araştırdınız?unclassified
“…Although echocardiography, computed tomography (CT), magnetic resonance imaging (MRI), and cardiac catheterization are currently used as the diagnostic tools of choice in children suspected of having congenital heart disease, chest radiography is still the most common initial study before referring specific investigation. For distinguishing children with congenital heart disease from normal children, the accuracy of chest radiography has been reported from 30 to 78 % in different clinical settings [4,5]. The discrepancy generally depends on the severity of disease, especially the hemodynamic status.…”
Section: Introductionmentioning
confidence: 99%